2015
DOI: 10.1007/s00330-015-4006-7
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of computed tomography-guided radiofrequency ablation of renal cancer: a 14-year single institution experience in 203 patients

Abstract: • Prognostic indicators for success of CT-guided RFA of renal tumours are reported. • Tumour size ≥3.5 cm confers an increased risk for residual tumour. • Clear cell renal cell carcinoma subtype confers increased risk for residual tumour. • Tmax <70 °C within the ablation zone confers increased risk for residual tumour. • Exophytic tumours have a lower probability of residual disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 37 publications
1
43
0
2
Order By: Relevance
“…mean frequency of 5.9 %. The following risk factors were described: (1) tumor size [2, 3, 13 -15], (2) central tumor location [3, 13 -15], (3) a maximum treatment temperature of ≤ 70°C [15], and (4) clear cell subtype of renal cell carcinoma [15]. The cutoff for tumor size defined as a risk factor was between 3 and 4 cm [3, 13 -15].…”
Section: Search Results and Baseline Characteristics Of The Included mentioning
confidence: 99%
“…mean frequency of 5.9 %. The following risk factors were described: (1) tumor size [2, 3, 13 -15], (2) central tumor location [3, 13 -15], (3) a maximum treatment temperature of ≤ 70°C [15], and (4) clear cell subtype of renal cell carcinoma [15]. The cutoff for tumor size defined as a risk factor was between 3 and 4 cm [3, 13 -15].…”
Section: Search Results and Baseline Characteristics Of The Included mentioning
confidence: 99%
“…Moreover, the follow-up was relatively short in comparison with the trials that investigated RFA and CRA of RCC. However, a study on a 14 year experience of RFA in the treatment of renal cancer has recently demonstrated that the majority of recurrences are detected within the first 24 months after the procedure, with a significant number being diagnosed within the first 3 months after the ablation sessions [45]. Therefore, it is likely that our median 26 month follow-up is long enough to infer good long-term efficacy of LA.…”
Section: Discussionmentioning
confidence: 98%
“…A total of 1,528 lesions were treated with an average tumor size of 2.5 cm (►Table 1). [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] Although the majority of studies involved percutaneous RFA alone (13), several studies (4) also included the combination of percutaneous and laparoscopic approach. Seventy-eight local recurrences were reported with a tumor recurrence rate of 5.0% (range: 0-15%) for percutaneous approach alone and 5.5% (range: 2.7-8.1%) for studies with a mixture of percutaneous and laparoscopic approaches.…”
Section: Review Of Contemporary Oncologic Outcomesmentioning
confidence: 99%